Gingival enlargement as oral manifestation in acute myeloid leukemia patient - Sandra Olivia Kuswandani; Yuniarti Soeroso; Sri Lelyati C. Masulili (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Acute myeloid leukemia (AML) is a bone marrow cancer, a malignant disease that triggering the cells develops into different types of blood cells. It is widely recognized that the main manifestation of AML could be gingival hyperplasia and bleeding. Occasionally, an initial diagnosis of leukemia is made after a dental examination. In relation to systemic diseases, gingival enlargement could constitute the intensification of an existing inflammation initiated by dental plaque, or a manifestation of the systemic disease independent of the inflammatory condition of the gingiva. Gingival enlargement negatively affects the quality of life, especially nutritional intake. Purpose: This study aimed to report on gingival enlargement in AML patients, dental management of this condition and considerations when treating patients. Case: A 46 year-old woman diagnosed with AML who chiefly complained of gingival enlargement in all parts of the mouth which restricted her nutritional intake. Case management: The subject attended the clinic twice where nonsurgical treatment for the gingival enlargement, supragingival scaling and dental health education to maintain her oral hygiene was carried out. Unfortunately, she did not return for follow-up appointments due to having already passed away. Information about AML and its relation to gingival enlargement contained in the literature is also reviewed. Conclusion: In conclusion, gingival enlargement represents one oral manifestation of AML. This condition is related to and affects the nutritional intake of the patient.